1930
DOI: 10.1017/s0370164600026481
|View full text |Cite
|
Sign up to set email alerts
|

XXV.—An Experimental Analysis of the Plumage of the Brown Leghorn Fowl

Abstract: General Summary1. The plumage of the Brown Leghorn fowl is analysed and the extent of its dependence on the activity of the thyroid and gonad is discussed.2. Hypothyroidism results (a) in a diminution in the amount of melanin and a coincident increase in the red pigment; (b) in an increase in the amount of fringing due to a lack of barbule formation. The female pattern tends to disappear.3. Hyperthyroidism in the male gives exactly the opposite effect—i.e. the melanin increases in amount while the red pigment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

1934
1934
1951
1951

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 8 publications
2
13
1
Order By: Relevance
“…They found that the resemblance to female feathers was much more striking in respect of shape and structure, but as related to colour there was an evident action towards the reduction of red pigment, varying in degree in different birds but tending to be arranged in " stippling " when present. These experiments were repeated on our own stock, but while our results agreed with the former in respect of changes of structure in the feathers from male to female type, it was not possible to confirm the opinion of Cole and Reid that the changes in patterning were suggestive of the pigment distribution found in the normal female (Greenwood and Blyth (1929)). Further, in the breast-a region which the previous authors did not discuss-there were never any indication of a tendency for the black to be replaced by the female colouration (red).…”
Section: R O Ycontrasting
confidence: 59%
See 2 more Smart Citations
“…They found that the resemblance to female feathers was much more striking in respect of shape and structure, but as related to colour there was an evident action towards the reduction of red pigment, varying in degree in different birds but tending to be arranged in " stippling " when present. These experiments were repeated on our own stock, but while our results agreed with the former in respect of changes of structure in the feathers from male to female type, it was not possible to confirm the opinion of Cole and Reid that the changes in patterning were suggestive of the pigment distribution found in the normal female (Greenwood and Blyth (1929)). Further, in the breast-a region which the previous authors did not discuss-there were never any indication of a tendency for the black to be replaced by the female colouration (red).…”
Section: R O Ycontrasting
confidence: 59%
“…It has been shown by various workers (Goodale (1916);Finlay (1925);and Greenwood and Blyth (1929)) that while the plumage of the normal female of this breed depends for the maintenance of its characteristic pattern and colour on the presence of ovary (secreting ovarian hormone), the plumage in the male is not significantly affected by the presence or absence of testis and is, in fact, of the neutral or asexual type exhibited by the completely gonadless bird of either sex. (The assumption of typical female plumage ensues as a result of the successful implantation of ovary into such individuals.…”
Section: Escription Of Plumagementioning
confidence: 82%
See 1 more Smart Citation
“…It may be considered that the action of oestrone is to inhibit the deposi tion of melanin in the feathers (Greenwood and Blyth, 1929); this action is practically complete in the breast region of the female but incomplete in other parts of the body such as the back and saddle where the melanin is restricted to fine broken lines resulting in a characteristic pencilled pattern. In females in which the black pigmentation is not entirely absent from the breast it is found to be concentrated mainly in the lateral feathers: faint stippled patterns occur, becoming more marked towards the outer edge of the tract, and always heavier on the outer (right) side of the feather, i.e., on the opposite side from that on which the half bar of red pigment was found in the experimental feathers.…”
Section: Greenwood Andmentioning
confidence: 99%
“…...the period for feather growth was shortened sig nificantly in the thyroid fed birds.... Greenwood and Blyth (1929) found feather growth slower in completely thyroidectomized birds. Chu (1938, p. 555) speaking of the period of time necessary for feather growth reported it "...lengthened in the thyroidectomized group.…”
Section: Io4mentioning
confidence: 89%